"How equity should assess a rate of interest against a defaulting trustee": investment performance of express trustees considered in the light of Watson v Kea. Issue 3 (2nd March 2020) - Graham, Toby; McPhail, Tom
Abstract: The Court of Appeal in Watson v Kea Investments [2019] EWCA Civ 1759 unanimously upheld an award of equitable interest of 6.5% compounded annually on the footing that the relevant inquiry for the Court was how equity should assess a rate of interest against a defaulting trustee. This article discusses how the Court determined the appropriate proxy basis for the award by reference to evidence adduced by the Claimant, Kea, and looks at potential ramifications for defaulting trustees in other contexts, including claims relating to poor investment performance of trust portfolios.